The Implementation of the Quantum Teaching Strategy with Multiple Intelligence Approach at State Senior High School - Basuki Tri Harnoto; Rahyu Setiani; B Widuroyekti; Dwi Sambada; Dwikoranto; Lindsay N. Bergsma (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2021)
The purpose of this research was to improve student learning outcomes, activities, and positive responses. Classroom action research carried out in 4 stages: planning, action and observation, reflection, and revision that carried out in three cycles. Data were collected through test, observation, questionnaire, and documentation. The participants of this research are class XI-3 students of State Senior High School 1 Krembung. Data were analyzed descriptively quantitative. Observation cycle 1, motivation by the teacher, learning objectives, explanation of working on worksheets, worksheet systematics, class control, seating settings, and intelligence use are lacking. The mean obtained is 55 with grade completeness of 38%. Observation cycle 2, delivery of learning objectives hastily, connecting material with daily phenomena is less clear, concluding that the material is not systematic. However, many students begin to maximize their intelligence to obtain a mean 63.75 with class completeness of 60%. Observation cycle 3 shows an improvement, and the process runs smoothly so that the mean is 74 with grade completeness 81%. Students' positive activity increased from cycle I to cycle III while learning achievement from cycle one to cycle three increased respectively by 38%, 60%, and 81%. The student’s response questionnaire showed that students had a positive attitude with 81.73% and 18.27% negative. In conclusion, student achievement and activity in learning had increased and received a positive response.